KONSUMERISME GENERASI MILENIAL DIERA DISRUPSI - Muhammad Iqbal Sanjaya (Institut Agama Islam Darul Ulum Kandangan, 2021)
Consumerism is excessive behavior in meeting the needs of life, especially in the era of disruption, everything changes so quickly, one of which is a shift in consumer behavior from traditional shopping culture to a digital system. The market share in the digital economy is dominated by the millennial generation. The millennial generation is expected to continue to hone skills and update literacy so as not to be carried away by uncertain currents and waves. In fact, long before this era of disruption, in the study of Islamic economics which was sourced from the values ??of the Qur'an, humans were taught not to be excessive or wasteful. As in Q.S al-A’raf: 31 dan Q.S al-Isra: 26-29.